Big data, small explanatory and predictive power: Lessons from random forest modeling of on-farm yield variability and implications for data-driven agronomy - Silva, ‪João Vasco; Heerwaarden, Joost van; Reidsma, Pytrik; Laborte, Alice G.; Tesfaye, Kindie; Ittersum, Martin K. van (Elsevier, 2023)
Context Collection and analysis of large volumes of on-farm production data are widely seen as key to understanding yield variability among farmers and improving resource-use efficiency.